Social representations about family care received by women crack users during hospitalization (Research, Society and Development, 2020)
To know the social representations of nurses who work in Maternity and Obstetric Center about family care received by women who are crack users during hospitalization in the sectors. Research with a qualitative approach. Its theoretical framework was the Theory of Social Representations. Participated 14 nurses who worked in the maternity and obstetric center of a hospital in southern Brazil. Data were collected in the second half of 2018, through semi-structured interviews and organized by the Collective Subject Discourse technique. The social representations are that most of these women face family problems, weakened ties, and do not have a consolidated family structure. They arrive at the service unaccompanied and are alone in the hospital. Some are accompanied by their mother or sister who are responsible for taking care of their child in the hospital and after discharge. Some are brought to the hospital or accompanied by friends, companions, pimps, clients and / or people who do not have blood ties. Many family members, too, are involved with drugs. The care for pregnant women who are crack users at the Maternity and Obstetric Center is complex, requiring training of the nursing team to address their need for assistance. She has not been able to exercise her right to a companion at the hospital, being necessary already during the prenatal period or when she is admitted to the hospital to capture a family member to be her support at this very important moment. It is believed that feeling supported can serve as a stimulus for this woman to reduce / avoid the use of crack and exercise motherhood in a more committed way.